Door Security System Using e-KTP and One Time Password (OTP) Code with Telegram Messenger Notification - Syalbilla, Putri Pajria (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2024)
The large number of cases of theft cases can be evidence that this crime is a social phenomenon that is always faced and always sought by various parties to reduce the intensity or level of crime that occurs. Improving the door security system is an effort that can be made to reduce theft that occurs because the existence of this door is often used by thieves as the main access to be able to enter a room and open it by breaking into the door. Therefore, the development of a door security system is needed to provide convenience in monitoring the condition of the door. This system is based on the NodeMCU ESP32 microcontroller as the working controller of the entire range, using the verification of the registered owner's e-KTP and OTP code as the second password to be able to open the door. Equipped with a solenoid door lock as door lock, magnetic sensor, SW 420 vibrating sensor, and buzzer as a security alarm. The Telegram application acts as a notification when there is an attempted theft or break-in on the door and as a messenger regarding who accesses the door. The test results obtained are tools that are designed as a whole to have good performance and can work according to their respective specifications, with the telegram application that can work optimally in monitoring all activities on the door. Keywords: RFID, e-KTP, One Time Password, NodeMCU ESP32, monitoring